Nicholas Eberstadt y Richard J. Ellings (eds.). Korea's Future and the Great Powers. Seattle: The National Bureau of Assian Research: University of Washington Press, 2001 - López Aymes, Juan Felipe (Estudios de Asia y África, 2002)
-